Yakup Kadri Karaosmanoğlu’nun “Hep O Şarkı” Adlı Romanında Soru Cümleleri - AZEEZ, HUDA HUSSEIN; Ali, Bushra Taher (Al-Adab Journal, 2020)
The purpose of the abstract: The Interrogative sentences are one of the more using sentences in the Turkish language & normal life in the Turkish society. For the reason, the basic purpose of this abstract; is the Interrogative study by its meaning and its linguistic structure. Upon y study, I focused on the interrogative sentences in a novel of (Jacob Qadri Kara Osman Oglu) under the title of (All This Song), I have selected this study because the author is one of novel name in the Turkish literature and also has been mentioned interrogative sentences largely for this novel. In Introduction or Preface, we mentioned to the meaning of interrogative sentences & its structure and we have dealt with value sources in the field of Turkish language for the Turkish linguists that they searched in the interrogative sentences generally.